2017
DOI: 10.1523/jneurosci.1739-17.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Endocannabinoid-Specific Impairment in Synaptic Plasticity in Striatum of Huntington's Disease Mouse Model

Abstract: Huntington's disease (HD) is an inherited neurodegenerative disease affecting predominantly striatum and cortex that results in motor and cognitive disorders. Before a motor phenotype, animal models of HD show aberrant cortical-striatal glutamate signaling. Here, we tested synaptic plasticity of cortical excitatory synapses onto striatal spiny projection neurons (SPNs) early in the YAC128 mouse model of HD. High-frequency stimulation-induced long-term depression, mediated by the endocannabinoid anandamide and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 56 publications
7
29
0
Order By: Relevance
“…In neurodegenerative diseases, such as Huntington disease, (Strand et al 2007;Zuccato and Cattaneo 2009;Park 2018;Yu et al 2018) and neurodevelopmental disorders (Autry and Monteggia 2012;Baydyuk and Xu 2014;Deinhardt and Chao 2014), BDNF release is strongly diminished. In the light of our results, this reduction of BDNF account for the reduction or the loss of synaptic plasticity, as observed in Huntington disease rodent models (Kolodziejczyk et al 2014;Plotkin et al 2014;Sepers et al 2018). On the opposite, BDNF levels are increased in maladaptive disorders such as ethanol or cocaine addiction (Jeanblanc et al 2009;Im et al 2010;Lu et al 2010;Bahi and Dreyer 2013) or neurogenetic disorders, such as DYT1 dystonia (Maltese et al, 2018).…”
Section: Discussionsupporting
confidence: 67%
“…In neurodegenerative diseases, such as Huntington disease, (Strand et al 2007;Zuccato and Cattaneo 2009;Park 2018;Yu et al 2018) and neurodevelopmental disorders (Autry and Monteggia 2012;Baydyuk and Xu 2014;Deinhardt and Chao 2014), BDNF release is strongly diminished. In the light of our results, this reduction of BDNF account for the reduction or the loss of synaptic plasticity, as observed in Huntington disease rodent models (Kolodziejczyk et al 2014;Plotkin et al 2014;Sepers et al 2018). On the opposite, BDNF levels are increased in maladaptive disorders such as ethanol or cocaine addiction (Jeanblanc et al 2009;Im et al 2010;Lu et al 2010;Bahi and Dreyer 2013) or neurogenetic disorders, such as DYT1 dystonia (Maltese et al, 2018).…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, deletion of striatal NMDAR abolished striatal LTP and impaired learning (Dang et al, 2006). Furthermore, R6/2 mice show less NMDAdependent LTP in the striatum compared to WT control (Kung et al, 2007) while deficit in endocannabinoid-dependent LTD was observed in the YAC128 mice (Sepers et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired cortico‐striatal plasticity has been reported in HD mice (Kung, Hassam, Morton, & Jones, ; Plotkin et al, ; Sepers et al, ). At early stages, both YAC128 and Q175/FDN iSPNs (Southwell et al, ) show impaired high‐frequency stimulation (HFS)‐induced LTD (Sepers et al, ), a presynaptically expressed form of LTD that results from postsynaptic activation of group I metabotropic glutamate receptors, D2 receptors, L‐type Ca2+ channels and calcium‐induced calcium release from Ryanodine receptors to synthesize anandamide. Anandamide binds to presynaptic CB1 receptors, decreasing glutamate release from cortical terminals (Lovinger, ).…”
Section: Altered Dopamine Signaling In Hd Mouse Modelsmentioning
confidence: 99%